ANALISIS KEPUASAN KERJA PNS DI DINAS KESEHATAN KABUPATEN TULANG BAWANG - Irianto Loka (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2011)
RACTTo increase the job satisfaction of civil servants is determined by several factors.Among the training and work environment that impact on the level of job satisfaction of acivil servant. One effort to achieve success is to increase the ability of an employee by wayof granting or implementing training in addition to environmental aspects that also needattention.From the analysis of data and testing hypotheses about the influence of trainingand working environment to the civil servant Job Satisfaction Tulang Bawang CountyGovernment Health Department obtained conclusion: Simultaneously EnvironmentalTraining and Employment has positive and significant impact on Job Satisfaction TulangBawang County Government Health Department. Partially each variable has a positiveand significant impact on job satisfaction.